Phytochemical Analysis, Antioxidant Activity and Bioassay-Guided Isolation of Acetylcholinesterase and Butyrylcholinesterase Inhibitors from Horsfieldia polyspherula Bark (Myristicaceae) - Mohammed Idris; Mohamad Nurul Azmi; Thaigarajan Parmusivam; Unang Supratman; Marc Litaudon; Khalijah Awang (Tropical Life Sciences Research, 2024)
Alzheimer’s disease (AD) is a neurodegenerative condition brought on by aging and characterised by progressive decline in cognitive function and abnormalities in the central cholnergic system. ?-amyloid deposits, neurofibril tangle aggregation, oxidative stress or reduced level of acetylcholine are a few causes that have been linked to AD. In this study, the bioassay-guided isolation from ethyl acetate (EtOAc) extract of Horsfieldia polyspherula bark led to the isolation of nine compounds namely, 16-phenylhexadecanoic acid (1), undecylbenzene (2), 3,4-dihydroxybenzoic acid (3), dodecanoic acid (4), tetradecanoic acid (5), pentadecanoic acid (6), 1-tridecene (7), stigmasterol (8) and trimyristin (9). Phytochemical analysis revealed the presence of flavonoids, steroids, lignin, alkaloids, phytosterol and triterpenoids. The DPPH scavenging activity of EtOAc extract was related to the phenolic content (116.67 ± 16.98 GAE mg/g) and other non-phenolics such as lower fatty acids. Meanwhile, the DPPH scavenging activity was found to be concentration-dependent and correlated with both flavonoid and phenolic content. Furthermore, EtOAc and methanol (MeOH) extracts of H. polyspherula bark showed significant inhibitory activity at 100 ?g/mL on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), with EtOAc extract showing 77.2% and 64.1% inhibition and MeOH extract showing 37.5% and 39.2% inhibition, respectively. Additionally, the IC50 for BuChE and AChE of the EtOAc extract were found to be effective, with 15.41 ± 0.78 ?g/mL and 7.67 ± 0.13 ?g/mL, respectively. Compound 1 exhibited dual inhibition of 40.99 ± 1.99 ?M (BuChE) and 46.83 ± 2.44 ?M (AChE), while compounds 2 and 3 showed IC50 values above 200 ?M. This study revealed that this plant shows a significant potential as anti-cholinesterase focusing on acetylcholinesterase (AchE) and butyrylcholinesterase (BuChE). This is the first report on Horsfieldia polyspherula and their biological activity.